Implementasi self management pada pasien dengan diabetes melitus - Nurliyani Nurliyani; Ririn Wulandari (Holistik Jurnal Kesehatan, 2022)
Background: Diabetes Mellitus Self Management An individual effort using therapeutic techniques that will be given as an intervention to control and direct oneself, and support behavior change towards a healthy lifestyle after being diagnosed with Diabetes mellitus (DM). Indonesia has around 9.1 million people with diabetes, it is estimated that by 2035, the number will reach 14.1 million. Lampung Province as a result of Riskesdes 2018 increased to 1.6%. Metro City for 2018 there are 798 DM women. The Margorejo Health Center itself is a new Public Health Center in 2018 , with 39 patients entering productive age women.Purpose: To obtain an overview or in-depth information about the patient's implementation of DM self-management in women of reproductive age.Method: Qualitatively using a phenomenological approach, with source triangulation technique. This research was conducted in the Margorejo Metro Selatan Public Health Center in February-March 2019. Sampling was carried out by purposive sampling, conducted by in-depth interviews with 5 main informants (women of productive age with diabetes mellitus), and 4 key informants (holders of diabetes mellitus). program at the Margorejo Health Center and 2 cadres).Results: The diet of DM patients in this study was still quite good. Sports/physical activity of DM patients in women of reproductive age is quite good. Blood sugar of DM patients in women of reproductive age has been well controlled. Treatment of DM patients in women of reproductive age is quite good. Problem-solving skills in women of reproductive age are quite good, it can be seen from the information conveyed that all informants handle DM so that diabetes is controlled by taking medication, eating patterns and resting regularly. Measurement of blood pressure and cholesterol levels has not been done properly. Reducing the risk of DM in women of childbearing age is good.Conclusion: Further research is needed to further examine the factors that may contribute to self-management such as stress experienced by DM patients.Keywords: Implementation; Patient; Self management; Diabetes mellitus; Woman; Productive agePendahuluan: Self Management Diabetes Melitus Sebuah usaha induvidu dengan menggunakan teknik terapeutik yang akan diberikan sebagai intervensi untuk mengendalikan dan mengarahkan diri, serta mendukung perubahan perilaku menuju pola hidup sehat setelah terdiagnosa Diabetes melitus (DM). Indonesia memiliki sekitar 9,1 juta pengidap diabetes, diperkirakan pada 2035, jumlahnya akan mencapai 14,1 juta. Provinsi Lampung hasil Riskesdes 2018 meningkat menjadi 1,6%. Kota Metro untuk tahun 2018 terdapat 798 wanita DM. Puskesmas Margorejo sendiri merupakan Puskesmas baru tahun 2018 ini dari pustu menjadi puskesmas, dengan untuk pasien yang masuk wanita usia produktif terdapat 39 pasien.Tujuan: Didapatkan gambaran atau informasi mendalam tentang Implementasi pasien terhadap self management DM pada wanita usia peroduktif.Metode: Kualitatif menggunakan pendekatan Phenomenologi, dengan teknih triangulasi sumber. Penelitian ini dilakukan di Wilayah Kerja Puskesmas Margorejo Metro Selatan Kota Metro pada bulan Febuari-Maret 2019. Pengambilan sampel dilakukan dengan cara purposive sampling, dilakukan dengan wawancara mendalam terhadap 5 orang informan utama ( wanita usia produktif penderita diabetes melitus), dan 4 orang informan kunci (pemegang program di Puskesmas Margorejo dan 2 orang kader).Hasil: Pola makan penderita DM dalam penelitian ini masih cukup baik. Olahraga/aktifitas fisik penderita DM pada wanita usia produktif cukup baik. Gula darah penderita DM pada wanita usia produktif sudah terkontrol dengan baik. Pengobatan penderita DM pada wanita usia produktif cukup baik. Keterampilan memecahan masalah pada wanita usia produktif sudah cukup baik telihat pada informasi yang tersampaikan bahwa seluruh informan menangani supaya DM terkontrol dengan meminum obat, pola makan dan istirahat dengan teratur. Pengukuran tekanan darah dan kadar kolesterol belum dilakukan secara baik. Mengurangi risiko penyakit DM pada wanita usia produktif sudah baik.Simpulan: Sangat diperlukan penelitian lanjutan untuk meneliti lebih lanjut faktor-faktor yang mungkin berkontribusi dalam self management seperti stres yang dialami pasien DM.